2013
DOI: 10.1074/jbc.m113.479584
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Heavy Chain-Hyaluronic Acid Polarizes Lipopolysaccharide-activated Macrophages toward M2 Phenotype

Abstract: Background: HC-HA is a unique anti-inflammatory matrix different from hyaluronic acid (HA). Results: Soluble HC-HA induces apoptosis of inflammatory neutrophils and macrophages, and immobilized HC-HA promotes M2 polarization upon LPS/TLR ligation while both enhancing macrophage phagocytosis. Conclusion: HC-HA exerts its anti-inflammatory action using multiple mechanisms. Significance: HC-HA is the first known matrix component to polarize M2b.Despite the known anti-inflammatory effect of amniotic membrane, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 90 publications
9
122
0
Order By: Relevance
“…The interaction between HC-HA and CD44 has been observed to promote CD44 "capping" and the digestion of HA by monocytes (32), which could release low molecular weight fragments that have been described as proinflammatory (33). That being said, there is evidence that monocyte incubation with HC-HA induces an anti-inflammatory M2 phenotype (34). This is supported by literature describing an anti-inflammatory role for TSG-6 in different disease models (10,35,36).…”
Section: Discussionsupporting
confidence: 69%
“…The interaction between HC-HA and CD44 has been observed to promote CD44 "capping" and the digestion of HA by monocytes (32), which could release low molecular weight fragments that have been described as proinflammatory (33). That being said, there is evidence that monocyte incubation with HC-HA induces an anti-inflammatory M2 phenotype (34). This is supported by literature describing an anti-inflammatory role for TSG-6 in different disease models (10,35,36).…”
Section: Discussionsupporting
confidence: 69%
“…This is particularly worrisome given that our laboratory and others have recently began to elucidate the mechanisms by which PTX3 preferentially increases IL-10 production from isolated PBMCs in normal-weight individuals, down-regulates the proinflammatory signaling cascade, and protects monocytederived macrophages from premature cellular death. 5,15,25,26 These findings have provided evidence to suggest that PTX3 aids in the polarization of monocytederived macrophages from an M1, pro-inflammatory, to an M2, anti-inflammatory phenotype, and thus, important mechanistic targets that may aid in the prevention in obesity-related pro-inflammatory disease, including CVD and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Once the tumor is established and LMW HA is chronically overproduced, it can promote immunosuppressive M2-like tumor-associated macrophage development (104), potentially through PGE 2 and IL-10 signaling as observed in our model. It has also been shown that HA of different sulfation states (106) or covalently linked with the heavy chain 1 of inter-␣-trypsin inhibitor (HC-HA) promotes M2 macrophage polarization (107) and acts in an antiinflammatory manner.…”
Section: Discussionmentioning
confidence: 99%